Efektivitas Perangkap Nyamuk Sederhana Berbahan Botol Bekas Dengan Larutan Gula Merah Dan Ragi Sebagai Upaya Pengendalian Vektor Chikungunya - Paputungan, Alvaizy Dwi Putra; Anhar, Ahmad Syaiful; Caesar, Adenova Revolino; Novendra, Carissa Shifa; Wardhana, Kaka Arya Putra; Hidayah, Laila Wahyu; Inayah, Adinda Nurul; Pratiwi, Andini Ayu; Tafuama, Franconero Nugroho; Notoar, Shafira Fajri; Muzamil, Sanupal (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Chikungunya is a disease caused by a virus transmitted through the bites of Aedes aegypti and Aedes albopictus mosquitoes. Vector control is a strategic step in preventing the spread of this disease. This study aims to evaluate the effectiveness of a simple mosquito trap made from used plastic bottles with a brown sugar and yeast solution in Dusun Suruh, Kopen Village, Teras District, Boyolali Regency, Central Java Province. The research method included the construction and placement of traps in several strategic locations and the observation of the number of mosquitoes captured over a specific period. The results showed that this trap was effective in attracting and capturing mosquitoes, with effectiveness influenced by environmental factors and the composition of the solution. Mosquito traps made from use plastic bottles with a brown sugar and yeast solution can serve as an affordable, eco-friendly, and easily applicable alternative for community-based vector control against chikungunya